Professionals' views on providing personalized recurrence risks for de novo mutations: Implications for genetic counseling - Kay, AC; Wells, J; Goriely, A; Hallowell, N (Wiley, 2024)
When an apparent de novo (new) genetic change has been identified as the cause of a serious genetic condition in a child, many couples would like to know the risk of this happening again in a future pregnancy. Current practice provides families with a population average risk of 1%–2%. However, this figure is not accurate for any specific couple, and yet, they are asked to make decisions about having another child and/or whether to have prenatal testing. The PREcision Genetic Counseling And REproduction (PREGCARE) study is a new personalized assessment strategy that refines a couple's recurrence risk prior to a new pregnancy, by analyzing several samples from the parent–child trio (blood, saliva, swabs, and father's sperm) using deep sequencing and haplotyping. Overall, this approach can reassure ~2/3 of couples who have a negligible (<0.1%) recurrence risk and focus support on those at higher risk (i.e. when mosaicism is identified in one of the parents). Here we present a qualitative interview study with UK clinical genetics professionals (n = 20), which investigate the potential implications of introducing such a strategy in genetics clinics. While thematic analysis of the interviews indicated perceived clinical utility, it also indicates a need to prepare couples for the psychosocial implications of parent‐of‐origin information and to support their understanding of the assessment being offered. When dealing with personalized reproductive risk, a traditional non‐directive approach may not meet the needs of practitioner and client(s) and shared decision‐making provides an additional framework that may relieve some patient burden. Further qualitative investigation with couples is planned.